2017
DOI: 10.1126/science.aam5298
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genomic changes associated with domestication of the horse

Abstract: The genomic changes underlying both early and late stages of horse domestication remain largely unknown. We examined the genomes of 14 early domestic horses from the Bronze and Iron Ages, dating to between ~4.1 and 2.3 thousand years before present. We find early domestication selection patterns supporting the neural crest hypothesis, which provides a unified developmental origin for common domestic traits. Within the past 2.3 thousand years, horses lost genetic diversity and archaic DNA tracts introgressed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(186 citation statements)
references
References 148 publications
3
170
1
6
Order By: Relevance
“…A corollary of this scenario regards the mutation load, which hitherto has been regarded as a “cost of domestication.” Under a continuous erosion of genetic diversity through repeated bottlenecks, we should expect a pattern in which mutation load increases over time. This notion is supported by recent findings in which the mutation load in horses was found to increase some time after domestication (Librado et al., ). In the case of sorghum, mutation load was found to increase over time and significantly correlate with signals of selection (Smith et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…A corollary of this scenario regards the mutation load, which hitherto has been regarded as a “cost of domestication.” Under a continuous erosion of genetic diversity through repeated bottlenecks, we should expect a pattern in which mutation load increases over time. This notion is supported by recent findings in which the mutation load in horses was found to increase some time after domestication (Librado et al., ). In the case of sorghum, mutation load was found to increase over time and significantly correlate with signals of selection (Smith et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of ancient DNA extracted from ancient maize, for example, have made it possible to track the appearance of specific domestication genes in this important crop plant as it moved from the heartland of initial domestication in southwestern Mexico up through central Mexico and into the southwestern USA [94,140,141]. Another recent study of ancient DNA extracted from horse skeletal remains finds evidence of enrichment for genes involved in androgen and steroid hormone receptor binding indicative of the selective pressures for behavioural and cognitive changes central to animal domestication [142]. This same study also found evidence for enrichment of genes affecting tissues and cell types derived from the neural crest that lends support for the hypothesis that the neural crest development is involved in the variety of associated traits commonly found in domestic animals [73].…”
Section: Directionalitymentioning
confidence: 99%
“…Admittedly, genealogies for significant candidate genomic regions identified by whole‐genome scans can be reconstructed and used to specify the branch on which a sweep most likely occurred (as in Fariello et al., ). Nonetheless, with a growing interest in evolutionary histories of ancestral populations (Basu, Sarkar‐Roy, & Majumder, ; Fraser, Künstner, Reznick, Dreyer, & Weigel, ; Johnson & Voight, ; Jones et al., ; Librado et al., ; Lindo et al., ; Mondal et al., ; Racimo et al., ), it is important to develop methods that can directly address hypotheses about shared ancestral selection, as they will permit ease of interpretation of candidate signals, and may exhibit improved power over methods that are not designed for this specific purpose.…”
Section: Introductionmentioning
confidence: 99%